One-part blast furnace slag mortars activated with almond-shell biomass ash: A new 100% waste-based material - Soriano, Lourdes (2020)
The use of almond-shell biomass ash (ABA) as an alkali source in one-part blast furnace slag (BFS) mortars activation was investigated for the first time. The chemical composition of ABA revealed high alkalinity ash to be composed mainly of K2O and CaO. The one-part 100% waste-based mortars and pastes were studied by mechanical and thermogravimetric tests. The compressive strength values of the newly designed materials were higher than the mortars fabricated with commercial products (36.4 versus 21.2 MPa). The formation of C-S-H/(C,K)-A-S-H gels took place in the thermogravimetric studies. The use of ABA in mortars proved an interesting alternative to chemical reagents in alkali activated cements.